Information technology for management : making connections for strategic advantage - Turban, Efraim; McLean, Ephraim; Wetherbe, James (New York : John Wiley and Sons, 1999)
This book is divided into four parts: IT in the organization; Networks and IT; Using IT; and Managing IT.
Keywords: Management; Information systems; Management information systems